Whole-Genome Patterns of Common DNA Variation in Three Human Populations - Hinds, David A.; Stuve, Laura L.; Nilsen, Geoffrey B.; Halperin, Eran; Eskin, Eleazar; Ballinger, Dennis G.; Frazer, Kelly A.; Cox, David R. (Science (American Association for the Advancement of Science), 2005)
Individual differences in DNA sequence are the genetic basis of human variability. We have characterized whole-genome patterns of common human DNA variation by genotyping 1,586,383 single-nucleotide polymorphisms (SNPs) in 71 Americans of European, African, and Asian ancestry. Our results indicate that these SNPs capture most common genetic variation as a result of linkage disequilibrium, the correlation among common SNP alleles. We observe a strong correlation between extended regions of linkage disequilibrium and functional genomic elements. Our data provide a tool for exploring many questions that remain regarding the causal role of common human DNA variation in complex human traits and for investigating the nature of genetic variation within and between human populations.